Epicutaneous sensitization in the development of food allergy: What is the evidence and how can this be prevented? - Brough, Helen A.; Nadeau, Kari C.; Sindher, Sayantani B.; Alkotob, Shifaa S.; Chan, Susan; Bahnson, Henry T.; Leung, Donald Y. M.; Lack, Gideon (Allergy (Copenhagen), 2020)
There is increasing evidence regarding the importance of allergic sensitization through the skin. In this review, we provide an overview of the atopic march and immune mechanism underlying the sensitization and effector phase of food allergy. We present experimental models and human data that support the concept of epicutaneous sensitization and how this forms one half of the dual‐allergen exposure hypothesis. We discuss specific important elements in the skin (FLG and other skin barrier gene mutations, Langerhans cells, type 2 innate lymphoid cells, IL‐33, TSLP) that have important roles in the development of allergic responses as well as the body of evidence on environmental allergen exposure and how this can sensitize an individual. Given the link between skin barrier impairment, atopic dermatitis, food allergy, allergic asthma, and allergic rhinitis, it is logical that restoring the skin barrier and prevention or treating atopic dermatitis would have beneficial effects on prevention of related allergic diseases, particularly food allergy. We present the experimental and human studies that have evaluated this approach and discuss various factors which may influence the success of these approaches, such as the type of emollient chosen for the intervention, the role of managing skin inflammation, and differences between primary and secondary prevention of atopic dermatitis to achieve the desired outcome.